Chemical-Vapor-Deposited Graphene as Charge Storage Layer in Flash Memory Device. (26th January 2016) - Liu, W. J.; Chen, L.; Zhou, P.; Sun, Q. Q.; Lu, H. L.; Ding, S. J.; Zhang, David W.
Abstract : We demonstrated a flash memory device with chemical-vapor-deposited graphene as a charge trapping layer. It was found that the average RMS roughness of block oxide on graphene storage layer can be significantly reduced from 5.9 nm to 0.5 nm by inserting a seed metal layer, which was verified by AFM measurements. The memory window is 5.6 V for a dual sweep of ±12 V at room temperature. Moreover, a reduced hysteresis at the low temperature was observed, indicative of water molecules or −OH groups between graphene and dielectric playing an important role in memory windows.